Thinking and Working Politically through Applied Political Economy Ana lysis. A guide for practitioners - Rocha Menocal, Alina; Cassidy, Marc; Swift, Sarah; Jacobstein, David; Rothblum, Corinne; Tservil, Ilona (USAID, 2018)
Thinking and Working Politically (TWP) through Applied Political Econo my Analysis (PEA). A guide for practitioners Have you ever done everyt hing right in a development program — followed every technical best pr actice — but still missed the mark? When this happens, it often relate s to factors in the context beyond any external development actor’s ab ility to control.